On the 12C Hoyle state gamma decay. (October 2020) - Cardella, G.; Favela, F.; Martorana, N.S.; Acosta, L.; Auditore, L.; Camaiani, A.; De Filippo, E.; De Luca, S.; Gelli, N.; Geraci, E.; Gnoffo, B.; Guazzoni, C.; et al.
Abstract: The γ-decays of 12 C excited levels (the Hoyle state 0 + at 7.65 MeV and the 9.64 MeV 3) are essential for its production in the universe. We present here a new attempt to precisely measure such γ-decay probabilities. The measurement was performed at INFN-LNS in Catania using the 4 π CHIMERA multidetector. In order to measure these low probability decay-channels we performed 4-fold coincidence measurements. The 12 C target nuclei were excited by using a beam of 64 MeV α-particles produced by the Superconducting Cyclotron (CS) of INFN-LNS. The scattered α-particles and the 12 C recoils were detected and identified by? E-E and ToF methods using CHIMERA telescopes. The two emitted γ-rays in the decay chain were detected and identified by using the second stage of the telescopes, CsI(Tl) scintillators, by means of fast-slow and rise time techniques. Kinematics and energy-momentum conservation laws were used to constrain the data analysis. Also the 3-α decay channel probability was measured. Such a simultaneous measurement of all known decay channels was useful to reduce the systematic errors. Preliminary results of the data analysis are reported.